Impaired Motor Learning Following a Pain Episode in Intact Rats - Huot-Lavoie, Maxime; Ting, Windsor Kwan-Chun; Demers, Maxime; Mercier, Catherine; Ethier, Christian (Frontiers in Neurology, 2019)
Motor learning and pain are important factors influencing rehabilitation. Despite being mostly studied independently from each other, important interactions exist between them in the context of spinal cord injury, whether to the spinal cord or the body. Ongoing or recent past episodes of nociceptive activity can prevent motor learning in spinalized rats. In intact animals, it has been proposed that supraspinal activity could counter the repressive effect of nociception on motor system plasticity, but this has not yet been verified in behavioral conditions. The aim of this study was to test whether a recent episode of nociception affects subsequent motor learning in intact animals. We trained rodents to walk on a custom-made horizontal ladder. After initial training, the rats underwent a week-long rest, during which they were randomly assigned to a control group, or one out of two pain conditions. Nociceptive stimuli of different durations were induced through capsaicin or Complete Freund's Adjuvant injections and timed so that the mechanical hypersensitivity had entirely subsided by the end of the resting period. Training then resumed on a modified version of the horizontal ladder. We evaluated the animals' ability to adapt to the modified task by measuring their transit time and paw misplacements over 4 days. Our results show that prior pain episodes do affect motor learning in neurologically intact rats. Motor learning deficits also seem to be influenced by the duration of the pain episode. Rats receiving a subcutaneous injection of capsaicin displayed immediate signs of mechanical hypersensitivity, which subsided rapidly. Nonetheless, they still showed learning deficits 24 h after injection. Rats who received a Complete Freund's Adjuvant injection displayed mechanical hypersensitivity for up to 7 days during the resting period. When trained on the modified ladder task upon returning to normal sensitivity levels, these rats exhibited more prolonged motor learning deficits, extending over 3 days. Our results suggest that prior pain episodes can negatively influence motor learning, and that the duration of the impairment relates to the duration of the pain episode. Our results highlight the importance of addressing pain together with motor training after injury.